Assessing soil erosion vulnerability using a novel capacity–condition framework (CCF): A case study from New South Wales, Australia - Hunakunti, Anilkumar; McBratney, Alex B.; Minasny, Budiman; Field, Damien J. (International Soil and Water Conservation Research, 2025)
Soil water erosion is a major threat to long-term soil sustainability. However, challenges remain in capturing how both natural and human-induced erosion processes interact over space and time to influence soil degradation. Current assessment methods often overlook how erosion simultaneously weakens the soil's inherent resistance (capacity) and degrades its current state (condition)-key drivers of long-term vulnerability and two core dimensions of soil security. To address this, we present a Capacity-Condition (CCF) framework, which quantifies erosion vulnerability using the erosion risk capability metric, which captures the gap between a soil's inherent resistance to erosion (capacity) and its erosion-altered state (condition). The framework employs the pedogeonon concept, identifying unique landscape units where the same soil-forming factors operate over time. Within each pedogeonon, two soil states are compared: genosoil (conditions influenced by natural erosion) and phenosoil (present state shaped by both natural and human-accelerated erosion). Capacity is assessed using genosoil indicators (clay ratio and topsoil thickness), and condition is evaluated using the phenosoil/genosoil ratio for the same indicators. Utility functions standardize these indicators on a 0–1 scale, enabling their aggregation into composite scores. When applied to New South Wales (NSW), Australia, the framework identified regions most vulnerable to erosion. Coastal areas and the upper northwest, characterized by intensive dry cropping and grazing on modified pastures, exhibited the highest risk values, indicating a lower capability to withstand future erosion. Conversely, regions with mixed land use-including grazing on native vegetation, intensive horticulture, and irrigated cropping-showed moderate risk, demonstrating the framework's utility for targeted, spatially explicit soil conservation and land management planning. [Display omitted]